2003
DOI: 10.1007/s00134-002-1576-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of discrepancies between clinical and autopsy diagnoses in the intensive care unit: a 5-year review

Abstract: Despite the availability of advanced diagnostic facilities, especially infectious complications seem to remain undiagnosed. Autopsy is a valuable tool with which to monitor diagnostic accuracy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 8 publications
(12 reference statements)
5
36
1
2
Order By: Relevance
“…These results are comparable with our previous study [13] where the discrepancy rate was 23%. Other studies have reported major diagnostic discrepancies in 5-40% of all hospitalised patients and in 7-32% of ICU patients [7,10,11,15,31,43,46,48,50]. These differences among studies may be explained not only by different ICU populations but also by differences in the indications for autopsy.…”
Section: Discussionmentioning
confidence: 97%
“…These results are comparable with our previous study [13] where the discrepancy rate was 23%. Other studies have reported major diagnostic discrepancies in 5-40% of all hospitalised patients and in 7-32% of ICU patients [7,10,11,15,31,43,46,48,50]. These differences among studies may be explained not only by different ICU populations but also by differences in the indications for autopsy.…”
Section: Discussionmentioning
confidence: 97%
“…This diversity may be due to difference in design of study, duration of study, type of underlying or immunosuppressive conditions and diagnosis methods. In addition, some authors suggested that invasive fungal infections are among the most commonly missed diagnoses in ICU patients (7,28,34).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, autopsy can provide additional information in more than one third of pediatric deaths, 40 including previously undiagnosed findings, complications, and unsuspected contributors to death. [41][42][43] This information may be of importance to parents and other relatives in future family planning and to physicians in helping to educate and improve the quality of care in medicine. Providing this information can help parents to make an informed decision when they are asked about permission for postmortem examination.…”
Section: Postmortem Examinations and Tissue And Organ Donationmentioning
confidence: 99%